Prevention of an Arms Race in Outer Space: Multilateral Negotiations’ Effects on International Law - T Vestner (Московский журнал международного права, 2020)
INTRODUCTION. Outer space is an increasingly competitive environment. This raises incentives for states to place conventional weapons in outer space. The 1967 Outer Space Treaty (OST), the applicable legal regime, is silent on the legality of the placement of conventional weapons, however. Since the early 1980’s, the multilateral diplomatic process on the Prevention of an Arms Race in Outer Space (PAROS) aims to explicitly prohibit the weaponization of outer space by a new international treaty. Yet states have not agreed on such a weapons ban treaty so far. This article analyses the multilateral negotiations’ effects on the applicable international law, namely the legal gap (lacuna) in the OST regime.MATERIALS AND METHODS. This study analyzes treaty texts, UN General Assembly resolutions, treaty proposals, states’ working papers, states’ statements, and reports from international negotiations and meetings. Th analytical framework is the rules for treaty interpretation according to the Vienna Convention on the Law of Treaties (VCLT). Consistent with explanatory and theory–building research, the methods used are those of historical legal research as well as general scientific methods, such as analysis, synthesis, analogy, description, and deduction.RESEARCH RESULTS. This article identifi s three mechanisms by which the multilateral negotiations on PAROS clarify and inform international law regarding the weaponization of outer space. First, the negotiations led states to communicate their legal positions regarding the issue. This clarifies how states interpret the law. It also allows to assess whether the continuous state practice to not place kinetic weapons in outer space represents subsequent practice of the OST according to Article 31(2)(b) VCLT. Second, the PAROS process produced annual UN General Assembly resolutions that strengthened the principle of peaceful use of outer space and linked it with states’ general understanding that this implies limits to the weaponization of outer space. As such, this is relevant for the interpretation of the gap in light of the OST’s context and object and purpose according to Article 31(1) VCLT. Third, the negotiations have produced precise language on a prohibition of weaponization in the form of the draft Treaty on Prevention of the Placement of Weapons in Outer Space and of the Threat or Use of Force Against Outer Space Objects (PPWT), which enables the emergence of a prohibition under customary international law. For the interpretation of the OST’s gap, this would constitute “any relevant rules of international law” according to Article 31(3)(c) VCLT.DISCUSSION AND CONCLUSIONS. This article argues that the multilateral negotiations have broken the legal silence regarding the placement of conventional weapons in outer space. While the three mechanisms help to identify and clarify the law, they also influence the material substance of the law. The PA-ROS negotiations have not led the existing law to clearly prohibit the weaponization of outer space. Yet the negotiations have informed the law such that the existing law hardly authorizes such action. The result is that the issue is unequivocally regulated by international law, i.e. the OST’s gap is undoubtedly a legal gap. Yet the Lotus principle according to which what is not prohibited under international law is authorized falls short of the existing legal situation. This suggests that lex ferenda, the law in the making, has effects on lex lata. Multilateral negotiations – even deadlocked or failed ones – thus may be more than the making of future law but also the shaping of existing law. Accordingly, ongoing multilateral negotiations might be analyzed as supplementary means of treaty interpretation according to Article 32 VCLT. For policymakers, this suggests that negotiations may be used to influence the existing law, even if reaching agreement on a new treaty is not possible.